Improving the sustainability of culinary MSMEs through e-commerce and capital management according to Islamic principles - Mais, Rimi Gusliana; Hidayat, Firman; Wulaningsih, Ririn Widyastuti; Prihatna, Nandang; Wulandari, Winda (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2024)
This study investigates the effectiveness of e-commerce in improving the performance of culinary micro, small, and medium enterprises (MSMEs) while addressing the technical challenges of using digital platforms. This study also explores how business owners manage their capital using Islamic principles and assesses their understanding and application of Islamic values in daily operations. Using a descriptive qualitative approach, data were gathered through observations, interviews, and documentation from culinary MSMEs in Setiamulya Village, Tarumajaya District, Bekasi, Indonesia. Informants were chosen to promote participatory observation and facilitate open communication. The findings reveal that while e-commerce presents significant benefits, several technical challenges—such as high advertising costs, missed notifications, and delivery issues—hinder its effectiveness. Most business owners diligently avoid interest-based loans in line with Islamic teachings; however, their understanding of riba (usury) is often incomplete. Although there are efforts to adhere to Islamic principles, there remains considerable room for improvement in their application. Public interest statement A stronger understanding of Islamic finance principles is also necessary to promote business sustainability. This study builds on previous research by highlighting the sustainability of culinary MSMEs from an Islamic perspective.